Usefulness of dynamic ultrasound in the diagnosis of epigastric herniation of stomach. (May 2022) - Corvino, Antonio; Corvino, Fabio; Tafuri, Domenico; Catalano, Orlando
Introduction: Abdominal wall hernia contents usually consist of omental or mesenteric fat or loops of small or large bowel. Gastric involvement has been only rarely reported. Case report: We present a case of a 62-year-old woman who was admitted to our hospital due to epigastric pain and vomiting. On physical examination, the only observed abnormality was a soft, painless, epigastric bulge located in the upper midline. Based on the clinical presentation, the patient was diagnosed with a probable epigastric hernia. Dynamic ultrasound evaluation of the palpable bulge confirmed the presence of epigastric hernia demonstrating the movement of abdominal contents through a large wall defect. Surprisingly, the herniated contents were found to contain also the anterior wall of the distal stomach together with omental fat and vessels. The patient opted for surgery, which confirmed the presence of an epigastric hernia containing the distal portion of stomach. Discussion: In this case, dynamic ultrasound provided added value over computed tomography by clearly demonstrating stomach passing from the abdominal cavity to enter into the hernia sac and it is therefore reported for both its rarity and interest. To our knowledge, this is the first such ultrasound-based case report presented in literature and certainly the best sonographically documented. Conclusion: We anticiapte that this case report will promote the use of dynamic ultrasound in current practice as an effective imaging tool to recognise unusual types of hernias.